Perspektiewe vanuit die psigologie en sosiale wetenskappe vir kerklike bediening aan die adolossent. Deel 2: Ondersoek na die leefwêreld van die adolessent - Erasmus, J. A. (Verbum et ecclesia, 2003)
In this article meta-theoretical perspectives for youth ministry are obtained specifically from the fields of psychology and sociology. In the first place, the various psychological development phases of the adolescent are determined, as well as how they have to be accounted for in youth ministry. In the second place, the characteristics of the world in which the adolescent lives are indicated together with their influence on the adolescents.